Faculty caring behaviors in online nursing education: an integrative review. Issue 4 (1st October 2020) - Jones, Kate; Raynor, Phyllis; Polyakova-Norwood, Vera
ABSTRACT: As online programs for nursing education continue to grow, nursing faculty must develop strategies for engaging with and supporting students in this form of distance learning. The concept of caring, which is central to nursing education, overlaps with teaching and social presence concepts from the community of inquiry model in education. After reviewing both distance education and nursing literature for background, we conducted an integrative review of studies focusing on online graduate nursing education. We found consistency in the types of faculty behaviors that were described, and that those behaviors aligned with our definition of caring. Implications for distance education include the need to better prepare faculty for online teaching so that they can be intentional about implementing caring behaviors when designing and delivering online education.